Konkurencyjność przepadku przedmiotów a przepadku korzyści majątkowej - Czwojda, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article contains the legal regulations regarding the forfeiture of objects and gains originating from crimes. It contains an analysis of the conditions for the application of forfeiture and the changes related to them. Particular attention was given to the competition between different types of forfeiture. The article presents an approach taking into account the positive changes and provides critical comments concerning some of the solutions. As a result, the considerations indicate the need of delimitation of forfeiture of objects and gains, complementing the regulatory deficiencies.
Keywords: przepadek korzyści majątkowej; przepadek przedmiotów; konkurencyjność